Kompetensi Manajerial Kepala Sekolah Di PAUD Ariya Kabupaten Kaur - Wahyuni, Seri (Manajer Pendididikan, 2024)
This research aims to implement the managerial competence of school principals in PAUD Ariya, Kaur district. The research uses qualitative descriptive methods. Research subjects were the principal, teachers and parents of students at PAUD Ariya Kaur. Research data was obtained from interviews, observation and documentation. Research data analysis includes data reduction, data presentation, verification and drawing conclusions. Based on the research results, it can be concluded that the principal at PAUD Ariya Kaur has comprehensive managerial competence. By combining several aspects, including PAUD principal Ariya Kaur, creating a balanced educational ecosystem, involving all stakeholders, and making information technology an effective tool to support early childhood learning.